Feeling connected to smart objects? A moderated mediation model of locus of agency, anthropomorphism, and sense of connectedness. Issue 133 (January 2020) - Kang, Hyunjin; Kim, Ki Joon
Highlights: User-agency elicits more positive responses from IoT users than object-agency. Perceived connectedness with IoT mediates the effect of locus of agency. IoT with human-like features provides users with greater perceived connectedness. Anthropomorphism of IoT moderates the mediating effect of perceived connectedness. Abstract: In human-IoT interaction, both users and smart objects can exercise agency. This study examines how the relationship between the locus of agency (user vs. object) and interaction outcomes is mediated through sense of connectedness and how this mediated relationship is moderated by anthropomorphic cues. Results from a lab experiment ( N = 94) indicate that users perceive their interactions more positively when they exercise their own agency than when the objects have agency. In addition, when the objects exert own agency, anthropomorphism elicits more positive user responses by increasing sense of connectedness.